Making libraries relevant : 2005 Knowledge Conference, 6-8 July 2005, Pustaka Negeri Sarawak, Sarawak, Malaysia - Knowledge Conference (2005 : Kuching); Pustaka Negeri Sarawak; Angkatan Zaman Mansang Sarawak ([Kuching] : Pustaka Negeri Sarawak, 2005)
Contained paper work for the knowledge conference includes it abstracts
Keywords: Libraries -- Congresses; Libraries -- Automation -- Congresses; Digital libraries -- Congresses; Library science -- Congresses